2014
DOI: 10.3928/01477447-20140401-61
|View full text |Cite
|
Sign up to set email alerts
|

Human Beta-Defensin-3 for the Diagnosis of Periprosthetic Joint Infection and Loosening

Abstract: In this study, the difference in expression of human beta-defensin-3 in periprosthetic tissue and cancellous bone was observed in the periprosthetic tissue and cancellous bone of patients in the periprosthetic joint infection group, the aseptic loosening group, and the spacer treatment group as well as the synovial membrane and ilium of the normal control group. Hematoxylin and eosin staining of the synovial tissue showed different levels of neutrophil infiltration in all groups except for the normal control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…However, CRP still plays its role as the most common systemic marker for differentiation between PJI and aseptic loosening with a reported possible diagnostic accuracy up to 84% [ 28 ]. In accordance with this study and others, CRP blood levels can be elevated [ 14 , 21 ]. However, interference with systemic diseases such as other infections, rheumatoid arthritis or gout lowers its specificity remarkably.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, CRP still plays its role as the most common systemic marker for differentiation between PJI and aseptic loosening with a reported possible diagnostic accuracy up to 84% [ 28 ]. In accordance with this study and others, CRP blood levels can be elevated [ 14 , 21 ]. However, interference with systemic diseases such as other infections, rheumatoid arthritis or gout lowers its specificity remarkably.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with our previous observations with synovial fluid [14]. Liu et al stated to have more HBD-3-positive cells with immunofluorescence staining of periprosthetic tissue in PJI compared to aseptic loosening or native joints [21]. However, information about the type of PJI (acute vs. low grade) and joints is missing, various CoNS and coagulase-positive staphylococcal pathogens up to three cases with uncultured bacteria have been pooled.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another study used immunofluorescence staining followed by a measurement of the mean optical density of the stained sections. This study reported highest hBD-3 values in septic loosening, and lower values in aseptic loosening, spacer group and normal controls [15]. In the work by Liu and co-workers, formalin-fixed and paraffin embedded tissue sections were analyzed using indirect immunofluorescence staining and fluorescence microscopy, but due to morphological restrictions of the analysis it was difficult to evaluate the cellular origin of hBD-3.…”
Section: Introductionmentioning
confidence: 72%